Թռչունների օրգաններից անջատած մանրէների նույնականացումը և հակաբիոտիկների նկատմամբ կայունության որոշումը - Շիրվանյան, Յու. Ա.; Արտուշյան, Ի. Ս.; Հովսեփյան, Լ. Մ.; Ղազարյան, Է. Օ. (ՀԱԱՀ հիմնադրամ)
Исследования показали, что каждый микроорганизм, выделенный у птиц, обладает характерны- ми для его вида морфологическими, биохимическими и тинкториальными свойствами. С помощью API-теста была проведена идентификация подтипов штаммов с точностью до 99.8 %. Чувствительность микроорганизмов к различным антибиотикам определяли диско-диффузионным методом. Множество микроорганизмов, выделенных от птиц, показали разную степень устойчивости к 28 антибиотикам итальянского производства. Примечательно, что ряд штаммов с патогенными свойствами проявили резистентность к 3 и более антибиотикам. Using research findings, it was determined that each strain exhibits distinct morphological, biochemical, and tinctorial attributes that are intrinsic to its particular classification. Remarkably, the API test proficiently categorized the subtypes of these strains, achieving an exceptional precision rate of up to 99.8 %. The following strains of microbes have been isolated during this study: E. coli, Salmonella Typhimurium, Staphylococcus spp., and Proteus mirabilis. The results of analyses conducted through the discօ diffusion technique reveal a diverse spectrum of antibiotic resistance profiles among the multiple strains isolated from poultry, encompassing 28 antibiotics originating from Italy. The acquired data are of significant scientific and pragmatic value. This underlines the need for specific emphasis on strains manifesting pathogenic traits, particularly those demonstrating multidrug resistance involving three or more distinct antibiotics. The importance of understanding and managing antibiotic resistance in avian microbial populations is underscored by this imperative.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն